NEW TYPES OF TRADEMARKS – PROTECTION OF MULTIMEDIA TRADEMARKS - George-Mihai IRIMESCU (Challenges of the Knowledge Society, 2019)
The Directive (EU) 2015/2436 of the European Parliament and of the Council of 16 December 2015 to approximate the laws of the Member States relating to trademarks.and the Regulation (EU) 2017/1001 of the European Parliament and of the Council of 14 June 2017 on the European Union trade mark changed one of the classical registration conditions for trademarks. More specifically, the graphical representation of the trademarks was replaced by the possibility to represent trademarks in a manner that enables the competent authorities and the public to determine the clear and precise subject matter of the protection afforded to its proprietor. This change enabled a more appropriate representation for sound marks, motion marks and holograms and, more important, made it possible to register a new type of trademarks – the multimedia trademarks. The complexity of multimedia trademarks could raise interesting practical challenges regarding their scope of protection, assesing their distinctiveness and their opposability. Moreover, given that such marks represent a combination of sound of images, the overlap with other intellectual property rights, such as copyrights, is more probable. Considering this element of novelty, this paper aism to analyze the early stages of the practice and anticipate potential challenges that multimedia trademarks would create, also based on the practice so far with respect to other types of non-traditional marks.